Emotional dimensions in integrated care for people with multiple complex problems - Anneli Hujala; Erja Oksman (Administrative Sciences, 2018)
Cross-boundary collaboration, both multiprofessional and interorganizational, is needed when providing integrated care for people with multiple problems, who need services at the same time from diverse care providers. Multiple problems of clients also pose extra challenges for interaction between care professionals and clients. Emotional dynamics are always present in everyday interaction between human beings, but seldom explicitly addressed in research on integrated care. The aim of this reflective paper is to illustrate the emotional dimensions of integrated care in light of the experiences of care professionals in the context of care for people with multiple complex problems. The paper draws on a Finnish study on integrated care reflecting its findings from the perspective of emotional labor. The difficult life situations of people with multiple complex problems form an emotional burden, which is mirrored in the interaction between clients and professionals and affects relational dynamics among professionals. Professionals' fear of emotions and the different 'feeling rules' of care professions and sectors pose extra challenges to professionals' collaboration in this emotionally loaded context. Alongside the structural and functional aspects of integrated care, it is important that emotions embedded in everyday cross-boundary collaboration are recognized and taken into account in order to ensure the success of integrated care.
Keywords: 350; integrated care; emotions; emotional labor; cross-boundary collaboration; care professional; patient; client; people with multiple complex problems; health and social care